Numerical Modeling of Hole Under Opposite Biaxial Loadings - Bouali Meriem Fakhreddine (Selected Scientific Papers: Journal of Civil Engineering, 2020)
The exact concentration of the stress generated by the presence of a cavity is a problem of great significance in Mining and Civil Engineering. An interesting stress concentration problem is the biaxial one. A numerical analysis of stress around a cylindrical hole in an infinite elastic medium under opposite biaxial loading was investigated. This far-field loading is equivalent to a pure shear loading on planes rotated 45°. Analysis consisted of two-dimensional finite-difference computations carried out with the Fast Lagrangian of Continua (FLAC) code. The Stress Concentration Factor (SFC) is evaluated numerically and compared with the existing solution. Predicted results of stress distribution around the hole were found in good agreement with the analytic theory.